Annual world Bank Conference on development Economics 1997 : [proceedings] - World Bank Annual Conference on development Economics Washington 1997; Stiglitz, Joseph E.; Pleskovic, Boris (Washington,D.C World Bank, 1998)
​The 1997 World Bank Conference on Development Economics held April 30-May 1, 1997, addressed four themes: corruption, incentives and performance in public organizations, the transferability of high-growth experience, and poverty and the environment. Though the articles in this report focus on a broad agenda for development--examining the role of national and international institutions in eliminating corruption and strengthening the rule of law, and in promoting sustainable development and raising living standards--several common themes unite them: What is the appropriate role of the government? How should incentives in the public sector be structured? and what are the relationships among economic growth, poverty, and environmental sustainability? The articles discuss the role of government as an institution and the need to reexamine how regulations and incentive structures can improve the effectiveness of government and the productivity of the economy. They also look at the experiences of high-growth economies to determine how transferable those experiences are to other developing countries. Furthermore, they emphasize the importance of strengthening institutional structures such as property rights and land tenure and of establishing new markets, all of which may positively affect the environment and improve the living conditions of the rural poor.
Introduction / Boris pleskovic and Joseph E.Stiglitz -- Corruption: catalysts and constraints: Corruption and development / Susan Rose- Ackerman -- What can be done about entrenched corruption? / Michael Johnston -- Incentives and performance in puplic organiztions: Incentive reforms in developing country bureaucracies: lessons from tax administration / Dilip Mookherjee -- incentives, efficiency, and government provision of public services / Sherwin Rosen and Bruce A. Weinberg -- Leaders in growth: can others follow?: What can developing countries learn from east Asian economic growth? Takatoshi Ito -- The political economy of high and low growth / Alberto Alesina -- Poverty and environment: Environment, poverty, and economic growth / Karl-Goran Maler -- Where development can or cannot go: the role of poverty-environment linkages / Ramon E. Lopez
Includes bibligraphies
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPMENT POLICY; CORRUPTION; POVERTY; ECONOMIC RESEARCH; DEVELOPING COUNTRIES; CONFERENCES